Clinical laboratory hematology reference values among infants aged 1month to 17 months in Kombewa Sub-County, Kisumu: A cross sectional study of rural population in Western Kenya. - Jew Ochola Ouma; David H Mulama; Lucas Otieno; John Owuoth; Bernhards Ogutu; Janet Oyieko; Jackson C Korir; Peter Sifuna; Valentine Singoei; Victorine Owira; Stacey Maureen Okallo Gondii; Ben Andagalu; et al. (PLoS ONE)
There is an urgent need for reliable region-specific hematological reference values for clinical monitoring. Laboratory reference ranges are important for assessing study participant eligibility, toxicity grading and management of adverse events in clinical trials and clinical diagnosis. Most clinical laboratories in Kenya rely on hematological reference values provided by instrument manufacturers and/or textbooks, which are based on population from Europe or North America. The use of such values in medical practice could result in improper patient management, selection bias in selection of appropriate participants for clinical trials and flawed classification of the clinical adverse events when applied to African populations. The aim of this study was to establish local laboratory hematological reference values in infants aged 1 month to 17 months from Kombewa Sub-county that could be true representative of the existing rural population. The study participants in the current study were those who had previously been recruited from GSK-sponsored study. This study was a phase III, Double Blind, Randomized, GSK-sponsored, Malaria Vaccine Clinical Trial that was conducted in infants aged 1month to 17months. 1,509 participants were included in the study analysis. Data were partitioned into 3 different age groups (1-6 months[m], 6-12 m and 12-17 m) and differences between gender were compared within each group. Data were analyzed using Graphpad prism V5 to generate 95% reference ranges (2.5th-97.5th percentile). There was evidence of gender differences in hemoglobin values (p = 0.0189) and platelet counts (p = 0.0005) in the 1 to 6m group. For the 12-17m group, there were differences in MCV (p<0.0001) and MCH (p = 0.0003). Comparing gender differences for all age groups, differences were noted in percent lymphocytes (p = 0.0396), percent monocytes (p = 0.0479), percent granulocytes (p = 0.0044), hemoglobin (p = 0.0204), hematocrit (p = 0.0448), MCV (p = 0.0092), MCH (p = 0.0089), MCHC (p = 0.0336) and absolute granulocytes (p = 0.0237). In 1 to 6m age group and all age groups assessed, for WBCs, hemoglobin, hematocrit, MCV and lymphocytes absolute counts, both 2.5th and 97.5th percentiles for Kisumu infants were higher than those from Kilifi. Platelet ranges for Kisumu children were narrower compared to Kilifi ranges. Kisumu hematology reference ranges were observed to be higher than the ranges of Tanzanian children for the WBCs, absolute lymphocyte and monocyte counts, hemoglobin, hematocrit and MCV. Higher ranges of WBCs, absolute lymphocyte and monocyte counts were observed compared to the values in US/Europe. Wider ranges were observed in hemoglobin, hematocrit, and MCV. Wider ranges were observed in platelet counts in Kisumu infants compared to the US/Europe ranges. Compared to Harriet Lane Handbook reference values that are used in the area, higher counts were observed in WBC counts, both absolute and percent lymphocyte counts, as well as monocyte counts for current study. Wider ranges were observed in RBC, platelets and RDW, while lower ranges noted in the current study for hemoglobin, hematocrit and granulocyte counts. This study underscores the importance of using locally established hematology reference ranges of different age groups in support of proper patient management and for clinical trials.